1996
DOI: 10.1007/bf00017816
|View full text |Cite
|
Sign up to set email alerts
|

Cold requirement for maximal activity of the bacterial ice nucleation protein INAZ in transgenic plants

Abstract: The bacterial ice nucleation gene inaZ confers production of ice nuclei when transferred into transgenic plants. Conditioning of the transformed plant tissue at temperatures near 0 degrees C greatly increased the ice nucleation activity in plants, and maximum ice nucleation activity was achieved only after low-temperature conditioning for about 48 h. Although the transgenic plants contain similar amounts of inaZ mRNA at both normal and low temperatures, low temperatures are required for accumulation of INAZ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…4; Table 5) (76), which may be due to improper protein folding or differences in posttranslational modification, especially since Xu et al (76) reported that ice nucleation activity decreased when the AfpA was deglycosylated experimentally. Another possibility is that highly active INPs and AFPs may be produced only at cold temperatures, as observed when inaZ was expressed in plants (65).…”
Section: Discussionmentioning
confidence: 99%
“…4; Table 5) (76), which may be due to improper protein folding or differences in posttranslational modification, especially since Xu et al (76) reported that ice nucleation activity decreased when the AfpA was deglycosylated experimentally. Another possibility is that highly active INPs and AFPs may be produced only at cold temperatures, as observed when inaZ was expressed in plants (65).…”
Section: Discussionmentioning
confidence: 99%
“…Previous SFG studies have shown that P. syringae and INPs anchored to the surface of hollow Escherichia coli cell envelopes can order water at the bacterial surface 31 33 , and that water interaction is enhanced close to the water melting point 31 , 34 . However, the molecular basis for water ordering and the mechanism behind the activation at low temperatures remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 It has also become evident that the ability of P. syringae InaZ to control water orientation is enhanced when cooled to temperatures close to the water melting point. 29,31 However, since bacterial cell surfaces contain a variety of many different proteins and other biomolecules, these studies could not track the molecular origin of this activation at the protein level. Our current picture of the interaction of INPros with water is still, to a large extent, based on theoretical models and molecular dynamics (MD) simulations 3,32,33 , with contradicting conclusions for protein folding and the role of side chain motifs.…”
Section: Introductionmentioning
confidence: 99%